The valuation relevance of credit ratings: empirical evidence from financial institutions around the world - Nyiama, J.; Lourenço, I.; Curto, J. (40th European Accounting Association Annual Congress, 2017)
This study investigates whether the market valuation of the two summary accounting measures, book value of equity and net income, is higher (lower) for the financial institutions positively (negatively) rated by the Moody’s and/or by the Standard and Poor’s, when compared to financial institutions that are not rated by these credit rating agencies. Findings suggest that positive ratings have an impact in valuation both in developed and emerging countries, and that in the case of emerging countries negative ratings do not impact market valuation significantly. Overall, the results are consistent with the idea that credit ratings are useful in reducing value uncertainty of the issuing firms and in mitigating information asymmetry in capital markets.